Invited review. Bond dissociation enthalpies in benzene derivatives and effect of substituents: an overview of density functional theory (B3LYP) based computational approach - Nam, Pham Cam; Quan, Vo Van; Thong, Nguyen Minh; Thu Thao, Phan Thi (Vietnam Journal of Chemistry, 2017)
In this review, we have mainly focused on the recent computational studies on the bond dissociation enthalpies (BDE) of the X‒H bonds of the para and meta substituted benzene derivatives (3Y-C6H4X‒H and 4Y-C6H4X‒H with X = O, S, Se, NH, PH, CH2, SiH2 and Y = H, F, Cl, CH3, OCH3, NH2, CF3, CN, NO2). In addition, the remote substituent effects on the BDE(X‒H), the radical stability and parent one have also been discussed in terms of the calculated ground state effect, radical effect and total effect. Model chemistry of ROB3LYP/6-311++G(d,p)//B3LYP/6-311G(d,p) can reproduce the BDE values with the accuracy of 1.0‒2.0 kcal/mol. The good linear correlations between Hammett constants and BDE values were discovered for both para and meta substitutions in phenols, thiophenols, benzeneselenols, anilines and phenylposphines with the R-squared lager than 0.94. In contrast, it does not occur in case of toluenes and phenylsilanes. Keywords. Benzene derivatives, density functional theory, bond dissociation enthalpies, substituent effects, radical effect, ground state effect, total effect, Hammett constants.